Volleyball fundamentals - Dearing, Joel. (Champaign, IL : Human Kinetics, 2003)
Presents an introduction to volleyball, discussing the basic features and rules of the game, and featuring diagrams, photographs, and explanations of various court positions and playing skills.
The W formation -- Creating topspin -- Serving -- Receiving serve -- Setting -- Attacking -- Blocking -- Digging -- Team defense -- Team offense -- Transition -- Modified games -- Scoring systems -- Off to the endline.
Keywords: Volleyball